2018
DOI: 10.18203/2320-1770.ijrcog20180200
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of skin disorders in pregnancy

Abstract: INTRODUCTIONVarious physiological adaptation of pregnancy related, immunological, metabolic, endocrine and vascular changes occurs during pregnancy which make the pregnant women susceptible to changes of skin and appendages.1 These changes can be categorised in three categories. First include various benign skin conditions due to physiological and hormonal changes like striae gravidarum, melasma, nail and vascular changes. Pre-existing skin conditions which flare-up during pregnancy included in second category… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 6 publications
(8 reference statements)
6
10
1
Order By: Relevance
“…~ 74 ~ Among the physiological changes, hyperpigmentation was commonest with linea nigra the most common pattern in 82% of the patients which is similar to study by Kumari et al [9] and Meena et al [13] where the most common pattern of hyperpigmentation was reported to be linea nigra in 91.4% and 88.5% of the patients respectively. Pigmentary changes predominated in second and third trimester because of surge of estrogen and progesterone, which are strong melanogenic stimulants, late in the pregnancy.…”
Section: Discussionsupporting
confidence: 77%
“…~ 74 ~ Among the physiological changes, hyperpigmentation was commonest with linea nigra the most common pattern in 82% of the patients which is similar to study by Kumari et al [9] and Meena et al [13] where the most common pattern of hyperpigmentation was reported to be linea nigra in 91.4% and 88.5% of the patients respectively. Pigmentary changes predominated in second and third trimester because of surge of estrogen and progesterone, which are strong melanogenic stimulants, late in the pregnancy.…”
Section: Discussionsupporting
confidence: 77%
“…This systematic review included 11 articles that met the eligibility criteria and were published between 2015 and 2021 (Table 1) [8][9][10][11][12][13][14][15][16][17][18]. In regard to the study designs of included articles, there were two cross-sectional studies [14,18], three cross-sectional were observational studies [10,16,17], one observational [8], one prospective observational cohort [9], one retrospective [11], and one prospective [13] whereas one study did not specify the design [12]. The total number of participants in the 11 studies was 14,813 participants, the least number of subjects included in a study was 100 pregnant women [12], and the largest number included was 9,679 [8].…”
Section: Resultsmentioning
confidence: 99%
“…The total number of participants in the 11 studies was 14,813 participants, the least number of subjects included in a study was 100 pregnant women [12], and the largest number included was 9,679 [8]. The included studies were conducted in only four countries; one study in Nigeria [9], one study in Libya [13], one study in Brazil [18], whereas the remaining eight studies were all in India [8,[10][11][12][15][16][17]. The overall major dermatological conditions during pregnancy were physiological skin changes [11][12][13][14][15][16][17][18] and pregnancy-specific dermatopathologies [8,9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations